Synthesis of Ni-zeolitic imidazolate framework embedded with graphitic carbon as multifunctional composite catalyst for electrochemical water splitting and photocatalytic clofibric acid degradation performance - Vijayakumar P.; Natesan K.; Athikesavan V.; Kumaravel S.; Raja A.; Kang M.; Krishnan P.S.; Yusuf K. (Elsevier Ltd, 2025)
Hydrogen possesses the capacity to function as an alternative energy source for fuel, and electrochemical water splitting is a very efficient method of hydrogen generation by electrolyzing water. The efficient and stable electrocatalysts consisting of elements common in the Earth's crust are necessary. The present study involves the fabrication of graphitic carbon nitride (C3N4) sheets incorporating nickel-zeolite imidazolate framework (Ni-ZIF) heterostructure (denoted as Ni-ZIF/CN) using a hydrothermal method. The resulting heterostructure exhibits an exceptionally lesser overpotential of ?54.53 mV and 280 mV to reach a current density of 10 mA cm?2 for hydrogen evolution reaction (HER) and oxygen evolution reaction (OER), respectively. The Tafel slope for the HER and OER in alkaline (1 M KOH) electrolyte is measured to be 128 mV dec?1 and 101 mV dec?1, respectively. These results surpass the performance of previously reported Ni-ZIF electrocatalysts. Mechanistic investigations suggest that the nanocomposite electrode exhibits significant inherent catalytic activity, mostly attributed to improved conductivity, easy electron transport, and a high number of active sites. Furthermore, the nickel foam (NF) electrode covered with Ni-ZIF/CN-100 catalyst demonstrates exceptional electrochemical stability for a duration of 100 and 72 h for HER and OER, respectively, during the amperometric i-t test. A maximum level of photocatalytic degradation was attained on the Ni-ZIF/CN-100 catalyst, reaching a percentage of 97.31%. This percentage remained constant at 90.78% even after eight consecutive runs. The excellent activity of the synthesized photocatalyst is mainly attributed to the excellent electronic interaction of Ni-ZIF with C3N4, which enhances its charge transfer and reduces the charge carrier recombination phenomenon. This study can potentially broaden the range of economically viable photo/electrocatalysts for the processes of water splitting and photocatalysis. ? 2024 Hydrogen Energy Publications LLC